Antibacterial and antioomycete activities of a novel designed RY12WY peptide against fish pathogens. (December 2020) - Hussain Bhat, Raja Aadil; Thakuria, Dimpal; Pant, Vinita; Khangembam, Victoria C.; Tandel, Ritesh Shantilal; Shahi, Neetu; Sarma, Debajit; Tripathi, Gayatri; Krishnani, Kishore Kumar; Krishna, Gopal
Abstract: In the present study, we have designed and synthesized a short compositionally simple peptide RY12WY having potent antimicrobial activity. The molecular docking study results showed that peptide has a strong affinity towards two protein targets of A. sobria ; aerolysin and outer membrane protein (OMP). The MIC values ranged from 0.98 to 500 μM and MBC values ranged from 4 to 650 μM against the selected bacterial and fungal pathogens. The intense antimicrobial activity of RY12WY is reported against A. sobria, A. hydrophila, E. tarda, S. aureus, V. parahaemolyticus, P. aeruginosa and E.coli at low concentration.The peptide also showed good activity against A. salmonicida and S. parasitica zoospores. The peptide retained its antimicrobial activity at higher temperatures. Besides, it was active in the presence of physiological salts and serum.The peptide showed negligible haemolytic activity at 125 μM and HC50 was found to be 1437.10 μM. The DNA binding assay indicated that peptide can bind with the genetic material of the bacteria and may inhibit its replication. The bacterial viability assay reported that the peptide interferes with bacterial membrane integrity. To conclude, the results suggest that RY12WY could be a promising therapeutic agent in aquaculture and has possible application in food processing industry which warrants higher temperatures. Highlights: A novel antimicrobial peptide, RY12WY was designed and synthesized with a net positive charge of +7. Molecular docking study revealed that peptide has a strong affinity towards two protein targets of Aeromonas sobria. The MIC and MBC values ranged from 0.98 to 500 µM and 4 to 650 µM respectively against the selected pathogens. The peptide was active in the presence of salts and serum and HC50 was found to be 1437.10 μM.